2012
DOI: 10.1002/pen.23386
|View full text |Cite
|
Sign up to set email alerts
|

Methods for quantifying the stable sintering region in laser sintered polyamide‐12

Abstract: Manufacturing complex parts by the laser sintering process requires a minimum amount of energy input for consolidation of polymer particles to occur; however too much energy can result in a decline in mechanical properties. This decrease is thought to be the result of polymer chain degradation. A stable sintering region (SSR) has been proposed to describe the optimum temperature range for successful laser sintering. This article will aim to quantify the SSR for polyamide‐12 by using thermogravimetric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 22 publications
3
49
2
Order By: Relevance
“…The upper limit is the temperature at which the 1% weight loss degradation occurs during a TGA experiment that is carried out from room temperature to HT at a heating rate of 10 ˚C x min -1 . This method clearly does not take into account the crystallisation effect present in semi-crystalline polymers such as PA based powders or PAEK materials and therefore according to Vasquez et al [9] can be used for more types of polymers. The authors showed that PA 12 presents a stable sintering region at 120˚C, with lower limit at 200˚C and upper limit at 320˚C.…”
Section: Stable Sintering Regionmentioning
confidence: 99%
See 4 more Smart Citations
“…The upper limit is the temperature at which the 1% weight loss degradation occurs during a TGA experiment that is carried out from room temperature to HT at a heating rate of 10 ˚C x min -1 . This method clearly does not take into account the crystallisation effect present in semi-crystalline polymers such as PA based powders or PAEK materials and therefore according to Vasquez et al [9] can be used for more types of polymers. The authors showed that PA 12 presents a stable sintering region at 120˚C, with lower limit at 200˚C and upper limit at 320˚C.…”
Section: Stable Sintering Regionmentioning
confidence: 99%
“…With this intent, Vasquez et al [9] defined the EMR for material degradation (EMR D ) (Eq.5) in the LS process using the volumetric energy density for degradation (ED vol,D ), the volume energy required to melt the powder material (E m ) and theoretical energy of degradation (per unit volume) (E D ).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations